Hybrid self-organization based facility layout planning - Potočnik, Primož (Strojniški vestnik, 2014)
A novel hybrid two-stage method of facility layout planning, based on self-organized clustering, is presented. In the first stage, a self-organizing map (SOM) is applied in order to organize the production process into production cells which encapsulate products with similar properties and similar machining requirements. In the second stage, the internal layout of each cell is optimized by an expert operator, taking into account various local restrictions, technological specifications, and methods of transportation. The method combines the advantages of both algorithmic and manual expert-based approaches to layout planning. The proposed method was applied in a real production company environment with promising results indicating a 42% reduction in intensity-length efficiency measure with respect to the current layout.
Keywords: celična proizvodnja; hibridna metoda postavitve; načrtovanje postavitve proizvodnje; nevronske mreže; optimiranje proizvodnje; samo-organizacija